PERANCANGAN ULANG UI/UX WEBSITE PENGOLAHAN SAMPAH MENGGUNAKAN METODE DESIGN THINKING (Startup XYZ) - Hisyam Hawari; Ahmad Musnansyah; Faishal Mufied Al Anshary (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The waste problem is a common problem and has become a universal phenomenon in various countries worldwide, including Indonesia. One way to reduce waste is to do waste management. Therefore, waste processing can be an excellent first step in preventing short-term and long-term waste. In today's modern era, information technology is growing rapidly. People can use this technological development to avoid waste in Indonesia with the presence of digital waste management services that all Indonesian people can use, one of which is the Xyz website. Xyz has a service to recycle the garbage sent from individual users and companies. However, from the results of website performance testing using the Single Ease Question measurement method that has been carried out, there are still several problems on the XYZ waste processing website, including Use of unfamiliar language, information that is difficult to reach, website flow that is too complicated, and some components of the interface design that website cannot use properly. So, it is necessary to redesign the user interface and user experience of the Xyz website using the design thinking method, which aims to improve the performance and usability of the Xyz website. Keywords— Garbage, User Experience, User Interface, Waste Management, Redesign